2021
DOI: 10.1002/jtr.2444
|View full text |Cite
|
Sign up to set email alerts
|

Social media usage behaviours of religious tourists: The cases of the Vatican, Mecca, and Jerusalem

Abstract: The study examines social media (SM) usage preferences of religious tourists, their motivations for sharing travel experiences on SM, and the motivational differences by demographics and SM usage characteristics. Employing three field studies in the Vatican, Mecca, and Jerusalem, we show that instant messaging applications were the most popular SM platforms for all religious groups. In addition, motivation for experience sharing on SM differed by age, visit frequency to destination, religiosity level, and SM u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…This function makes social media a new platform for consumer socialisation and exchange of opinions freely. It has also become an unconventional channel for marketing strategy development and for shaping consumer perceptions and behaviours (Caber et al, 2021). Social media plays a very important marketing role in the medical tourism industry.…”
Section: Social Media Communicationmentioning
confidence: 99%
“…This function makes social media a new platform for consumer socialisation and exchange of opinions freely. It has also become an unconventional channel for marketing strategy development and for shaping consumer perceptions and behaviours (Caber et al, 2021). Social media plays a very important marketing role in the medical tourism industry.…”
Section: Social Media Communicationmentioning
confidence: 99%
“…Therefore, at the end of war or in times of separation and unrest, the number of places of worship will increase rapidly. The religion in this period can make up for the problems of multi-ethnic integration caused by the war (Karklins and Zepa, 1996), and the government will increase its support for religion to achieve multi-ethnic integration and exchange, so as to maintain new social relations and personal friendship (Caber et al, 2021). The Northern Wei Dynasty, Yuan Dynasty and Qing Dynasty in this paper are typical representative dynasties.…”
Section: Discussionmentioning
confidence: 97%
“…It is a multi-functional place for cultural propaganda, religious dissemination, knowledge popularization and assembly organization [2]. The concept that some famous religious sites are called sacred sites or holy ground has always been an important aspect of some major religions in the world [3]. It is a place where believers yearn for protection and explain their beliefs after being challenged or pressured.…”
Section: Introductionmentioning
confidence: 99%
“…Research interest in religious tourists' behaviour on digital platforms, such as social media and social networking sites, remains incipient. Caber et al (2021) have identified a few early works, such as Haq and Jackson (2009) investigating the impact of ICTs on religious tourists' perceptions and Park et al (2015) surveying American participants to gauge their interest in visiting pilgrimage destinations and willingness to share their experiences on social networking sites.…”
Section: Pilgrimage Tourism's Digital Footprintmentioning
confidence: 99%
“…The relationship between tourism and pilgrimages has been studied in a fragmentary manner (Caber et al, 2021), despite the growing economic importance of this kind of tourism [1]. While motivations and experiences have been analysed (Terzidou et al, 2018), limited attention has been paid to behaviour on online platforms and digital devices (de Ascaniis et al, 2019).…”
Section: Introductionmentioning
confidence: 99%